Analysis of the Effectiveness of Programs Designed for Prevention of Deviant Behavior in Educational Institutions for Adolescents - Brigadirenko, N.V.; Gorina, A.L.; Dementyev, A.S.; Kimstach, E.L.; Konovalov, A.Y.; Kupriyanova, E.A.; Sidorenko, Z.M.; Stratiychuk, E.V.; Chirkina, R.V. (Bulletin of Practical Psychology of Education, 2024)
Approbation and implementation of new technologies of social risk prevention in special educational institutions for young offenders should be beforehand substantiated by evidence-based research on their effectiveness. The article presents the results of the research on the dynamics of parameters significant for the prevention of deviant behavior of adolescents, obtained during the two-year testing of the model Ecosystem of Childhood. It´s a systemic model of social risk prevention in the Centers for Assistance to Family Education in the city of Moscow. Model included all levels of prevention, it is mostly focused on working with adolescents with maladaptation). Significant changes in coping strategies, the level of satisfaction of basic needs, and other convincing results of the study brought us to testing the most effective elements of this model in other institutions, in this case closed schools for young offenders. Among them restorative practices (Community Circle Counseling, etc.), the author's method of individual-personal support (mentoring), the Skillful Class/Skillful Group technology developed by Ben Furman, and other soulution-focused methods. Апробация и внедрение новых технологий профилактики социальных рисков в специальных учебно-воспитательных учреждениях для несовершеннолетних с девиантным поведением предполагает, что эти процессы должны быть обоснованы доказательными исследованиями эффективности предлагаемых практик и технологий. В статье представлены результаты исследования динамики параметров, значимых для профилактики девиантного поведения подростков. Результаты получили путем двухлетней апробации модели профилактики социальных рисков «Экосистема детства». Модель включала все уровни профилактики, но в большей степени была нацелена на работу с подростками, проявляющими признаки дезадаптации, отклоняющееся поведение, учебные трудности, самовольные уходы и др. Значимое изменение копинг-стратегий, уровня удовлетворенности базовых потребностей и другие убедительные результаты исследования стали основой для апробации на базе СУВУ закрытого типа наиболее эффективных системообразующих элементов этой модели, в число которых вошли восстановительные практики, навыковые технологии на основе ОРКТ и индивидуальное профессионально-личностное сопровождение - менторинг.